Do Kindergarteners Develop Awareness of the Statistical Regularities They Acquire?. Issue 2 (14th January 2021) - Spit, Sybren; Andringa, Sible; Rispens, Judith; Aboh, Enoch O.
Abstract: Many studies suggest that detecting statistical regularities in linguistic input plays a key role in language acquisition. Although statistical learning is not necessarily implicit in nature, it is often defined as learning that happens without awareness. This article investigates whether statistical learning in young children is indeed implicit, as often assumed. We trained 63 kindergarteners on a miniature language and assessed learning using a picture‐matching task. We used an opt‐out task to measure whether the kindergarteners possessed awareness of an acquired meaningful grammatical marker. In the opt‐out paradigm, participants demonstrate awareness by expressing uncertainty through a nonverbal response: opting out. Our results are compatible with an earlier study of which the present study is a partial replication, suggesting that kindergarteners can acquire this marker from distributional properties in the input. Furthermore, although none of the children could verbalize knowledge of the structure during exit interviews, their behavior during the opt‐out task indicated that they developed awareness of it. Abstract :